If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(q + 9) = 2 Reorder the terms: -2(9 + q) = 2 (9 * -2 + q * -2) = 2 (-18 + -2q) = 2 Solving -18 + -2q = 2 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -2q = 2 + 18 Combine like terms: -18 + 18 = 0 0 + -2q = 2 + 18 -2q = 2 + 18 Combine like terms: 2 + 18 = 20 -2q = 20 Divide each side by '-2'. q = -10 Simplifying q = -10
| 3/8=a/8 | | -5p+17=-18 | | 4(3x-1)=5x+6 | | 4/15-2/3 | | (x/2)-15=125 | | 2z-2x+2y+2z^3=0 | | -.75x+6=-12 | | 1h+7=17 | | v(x)=(12-2x)(16-2x)(x) | | 10k-11k=20 | | 0x+2y+2z=0 | | -2x+x-5=3x+3 | | k(x)=3(x-1)(x+1) | | 1.06(1.26)(7-x)=8 | | -3r+7-7=13-7 | | 1.06(1.26)77-x=8 | | (2x^2)+2+14x=90 | | y=2+13y | | 20x+y=180 | | 12x+6x^2=9x^2 | | 2(5x+3)=x+6(x+1) | | 7y+3x=58 | | -3/7(2)-2=y | | 7+63y= | | 6p-8p+-5=-17 | | 55m+5= | | 7x+4+5x+3+2+5=180 | | .80(5-20x)=-44 | | (-3)^5/(-3)^8 | | 102=-3(6n-4) | | h(x)=(2x+5)(3x-1) | | 7^5/7^3 |